2002
DOI: 10.3758/cabn.2.3.264
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal cortex and dynamic filtering of emotional stimuli

Abstract: Event-related potentials (ERPs) were recorded in response to mildly aversive somatosensory and auditory stimuli. Patients with orbitofrontal lesions exhibited enhanced ERPs (i.e., P3 amplitudes), as compared with control subjects. Moreover, these patients did not habituate to somatosensory stimuli across blocks of trials. The results were specific to orbitofrontal damage, since patients with damage to the dorsolateral prefrontal cortex did not exhibit enhanced P3 amplitudes. These findings suggest that damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
96
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 33 publications
13
96
0
2
Order By: Relevance
“…Thus, this is not an instance of patients showing a peculiar idiosyncratic response but, rather, a difference in amount. Our findings of greater self-reported fear and greater surprise behavior for patients are consistent with the findings of Rule, Shimamura, and Knight (2002), which showed that patients with orbitofrontal damage show central nervous system disinhibition. Our findings also lend support to the notion that the orbitofrontal cortex may act as a filtering system for sensory inputs (Shimamura, 2000).…”
Section: Reactions To Unanticipated Acoustic Startlesupporting
confidence: 82%
“…Thus, this is not an instance of patients showing a peculiar idiosyncratic response but, rather, a difference in amount. Our findings of greater self-reported fear and greater surprise behavior for patients are consistent with the findings of Rule, Shimamura, and Knight (2002), which showed that patients with orbitofrontal damage show central nervous system disinhibition. Our findings also lend support to the notion that the orbitofrontal cortex may act as a filtering system for sensory inputs (Shimamura, 2000).…”
Section: Reactions To Unanticipated Acoustic Startlesupporting
confidence: 82%
“…This would further attenuate the overall P3b amplitude for 785 the first informational image in response to ETs in the exclusion block and minimize the effect that was evidenced in the shorter exclusion manipulations used previously (Crowley et al, 2010;Themanson et al, 2013). Evidence for this habituation and desen-790 sitization of ERPs has been found in other areas of P3b research (Rule, Shimamura, & Knight, 2002) and has been suggested for other exclusion-related ERP effects (Crowley et al, 2010). It is important to note that the decrease in P3b amplitude over the course of 795 the exclusion may not reflect habituation.…”
Section: Neural Activity During First Informational Imagementioning
confidence: 88%
“…Consistent with this possibility are the results of a recent functional magnetic resonance imaging (fMRI) study with only ENN_E and ENN_N trials (Johnson et al, 2005, Experiment 6B). There was more activity in the orbitofrontal cortex, an area thought to play a role in inhibitory processes (e.g., Rule, Shimamura, & Knight, 2002), when a neutral item was refreshed than when an emotional item was refreshed. Johnson et al (2005) referred to the disruptive effect of an emotional item on the refreshing of a target item as an instance of mental rubbernecking.…”
Section: Discussionmentioning
confidence: 99%